Digitalization of Agriculture in The Context of Ensuring Food Security - Svetlana FILIPPOVA; Evgenij IVANOV; Larisa GORDEEVA; Marina ABROSIMOVA; Olga LITVINOVA; Marie TOLSTOVA; Оlesya AFANASIEVA; Natalia NESTEROVA (Communications of International Proceedings, 2021)
The article reviews theoretical approaches to the study of the issue of digital transformation of food systems, identifies innovative trends associated with increase in demand for food, in the context of decrease in resources, increase in urbanization and change in the value orientations of population. World trends in the development of digital technologies in the field of agricultural production in the modern world economy were studied. Analysis of the size and structure of global investments in the business models of consumer technologies was made: “from market to plate” (downstream) and industrial technologies “from farm to market” (upstream). The impact of digital technologies on the production of agricultural products and food in the world was assessed using indicators of agricultural development, and the level of the economy innovativeness determined through the global innovation index. It was concluded that global food security will be ensured by those countries that provide food not only for their citizens, but also for other countries.
Keywords: Global Investments; Agricultural Technologies; Digital Technologies; Consumer Technologies (Downstream); Industrial Technologies (Upstream)